Effects of pyrolysis temperature on the physicochemical properties of biochar derived from vermicompost and its potential use as an environmental amendment. Issue 50 (4th June 2015) - Yang, Gang; Wang, Zhanghong; Xian, Qiming; Shen, Fei; Sun, Cheng; Zhang, Yanzong; Wu, Jun
<x xml:space="preserve">Abstract</x> Biochar derived from vermicompost can be employed as an excellent adsorbent for removing contaminants from aqueous solutions.